2021
DOI: 10.3390/life11040326
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation and Chronic Inflammation—Molecules and Mechanisms Involved in Skin Carcinogenesis: A Narrative Review

Abstract: The process of skin carcinogenesis is still not fully understood. Both experimental and epidemiological evidence indicate that chronic inflammation is one of the hallmarks of microenvironmental-agent-mediated skin cancers and contributes to its development. Maintaining an inflammatory microenvironment is a condition leading to tumor formation. Multiple studies focus on the molecular pathways activating tumorigenesis by inflammation and indicate several biomarkers and factors that can improve diagnostic and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 127 publications
(150 reference statements)
1
33
0
Order By: Relevance
“…UVB irradiation of skin cells leads to excessive ROS production and, consequently, to damage of biomolecules present in the cell membrane, disturbances in cell metabolism and enzyme secretion [ 2 ]. In the present study, FBBP effect on intracellular ROS and malondialdehyde (MDA) production was investigated, for the first time, in both experimental models of oxidative stressed fibroblasts and keratinocytes, in regard of their role as protective agents against oxidative damage and lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UVB irradiation of skin cells leads to excessive ROS production and, consequently, to damage of biomolecules present in the cell membrane, disturbances in cell metabolism and enzyme secretion [ 2 ]. In the present study, FBBP effect on intracellular ROS and malondialdehyde (MDA) production was investigated, for the first time, in both experimental models of oxidative stressed fibroblasts and keratinocytes, in regard of their role as protective agents against oxidative damage and lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, The International Agency for Research on Cancer classified UV radiation as carcinogenic to humans. Studies have shown that prolonged exposure to UV radiation triggered the activation of cytokines and growth factor receptors, leading to an inflammatory response and overexpression of metalloproteinases (MMPs), such as collagenases (MMP-1 and MMP-8), stromelysin (MMP-3) and gelatinases (MMP-2 and MMP-9), involved in the degradation of the extracellular matrix and, consequently, causing connective tissue remodeling [ 2 ]. Among the three types of UV radiation, UVB is known to be responsible for cancer and other skin conditions due to penetration of epidermis and upper dermis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation also initiates the activation of both inflammation and pro-inflammatory cytokine secretions, such as interleukin-2 (IL-2) and interleukin-6 (IL-6) [36]. As a result, this UVR-induced inflammatory response has an important role on the induction of burned skin with signs of redness, irritation, and erythema [35,[57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DNA damage triggered by ROS exposure can interfere with the ability of certain epigenetic regulators to bind to DNA, leading to abnormal DNA methylation patterns and altered gene expression [ 84 ]. Additionally, long-term production and accumulation of cytokines and ROS/reactive nitrogen species (RNS) have been correlated with the activation of STAT3 and NF-κB oncogenic pathways in epithelial cells [ 27 , 85 ]. In parallel, antigen-presenting cells (APCs) and cytokines can activate T cells, involving transcription factors that participate in their transcriptomic reprogramming, which includes epigenetic changes, among others [ 80 ].…”
Section: CM Epigeneticsmentioning
confidence: 99%
“…Multiple environmental agents can induce inflammation; however, UV radiation remains the most prominent aggressor, resulting in significant DNA damage and reactive oxygen species (ROS) generation [ 26 ]. Inflammation has acute and chronic stages that can shift the physiological balance towards skin regeneration or tumorigenesis, depending on their intensities [ 18 , 27 ]. If the inflammation is persistent and acquires chronic attributes, it may lead to a pre-cancerous lesion in the form of a dysplastic nevus.…”
Section: Introductionmentioning
confidence: 99%